Cognitive and emotional empathy in patients with schizophrenia spectrum disorders: A replication and extension study. (June 2019) - Berger, Philipp; Bitsch, Florian; Jakobi, Babette; Nagels, Arne; Straube, Benjamin; Falkenberg, Irina
Highlights: Independent replication of Lehmann et al. (2014, Psychiatry Res., 220 (3), 825–833). Impaired cognitive empathy, but preserved emotional empathy in patients with schizophrenia spectrum disorders. Associations between emotional empathy and (social) anhedonia in patients. Abstract: Impairments of social cognition are defined as core features in the pathology of schizophrenia. In a study by Lehmann and colleagues (2014), patients with schizophrenia have been shown to demonstrate a diminished capacity to understand others' emotions (i.e. cognitive empathy), but a preserved ability to share or feel the emotional states of others (i.e. emotional empathy). Here, we report on an independent replication study investigating cognitive and emotional empathy in 35 patients with schizophrenia spectrum disorders and a matched control group, which 1) confirms that patients demonstrate preserved emotional empathy in self-report and behavioural measurements, and 2) reveals associations between emotional empathy and social anhedonia in patients.